Exploring Indonesian fathers’ educational needs in newborn care: A qualitative study - Agustina, Ayuda Nia; Pratiwi, Anggi; Mahardika, Putri (Belitung Nursing Journal, 2026)
Background: Father involvement in newborn care is increasingly recognized as a key determinant of infant health and family well-being. In Indonesia, paternal roles in neonatal care are often overlooked, and father-specific educational support remains limited. Understanding fathers’ lived experiences and learning needs is essential for developing effective, culturally appropriate interventions. Objective: This study aimed to explore the experiences and educational needs of Indonesian fathers in newborn care. Methods: A qualitative descriptive study was conducted using a thematic analysis approach. Sixteen fathers of infants aged 0-12 months were recruited through purposive sampling in Jakarta and the surrounding areas. Data were collected in 2024 through in-depth semi-structured interviews and analyzed using Braun and Clarke’s six-step framework. Trustworthiness was ensured through audit trails, member checking, and peer debriefing. Results: Three major themes emerged: (1) social media as the main source of information, (2) fathers’ practical involvement and learning needs in baby care, and (3) preference for visual and practical learning media. Fathers expressed strong motivation to be involved but faced challenges accessing reliable, father-focused educational content. Their learning preferences were shaped by practicality, time constraints, and the need for culturally relevant materials. Conclusion: Indonesian fathers are eager to participate in newborn care but lack structured educational support tailored to their needs. Pediatric nurses play a critical role in developing father-inclusive, digital, and culturally responsive interventions that enhance paternal self-efficacy and caregiving competence. Future programs should integrate father-focused digital interventions, such as video-based tutorials and podcasts, into pediatric nursing practice to effectively bridge the educational gap.